Influência da irradiação do laser vermelho na percepção da dor de puérperas com lesão mamilar na amamentação: ensaio clínico duplo cego randomizado e controlado - Sartorio, Barbara Tideman [UNIFESP] (2018)
Introduction: Breastfeeding is an indispensable practice and is considered the best way to feed the child. However, early weaning, mainly due to the occurrence of nipple lesions, is an important public health problem. The treatment of these lesions is a major challenge today due to the scarcity of literature on the subject.The use of laser in nipple lesions was studied by three publications and in continuity a new therapeutical proposal with red laser was tested. Objectives: To evaluate the degree of pain in women with nipple lesion and to compare the effect of laser irradiation with 2 Joules of energy protocol, red wavelength, on pain during feeding, between control and intervention groups. Method: Clinical trial, doubleblind, randomized and controlled, performed at the Maternity Unit of the Amparo Maternal Hospital Santa Catarina Congregation Association (ACSC). 75 postpartum women were included, which were divided between the groups (Control/Intervention). The proposed therapy was a single irradiation of 2 Joules of the InGaAlP red laser under punctual application in the skin contact mode, at the center of the lesion, lasting 20 seconds, with optical power of 100 mW. The evaluation of the analgesic response was performed using the Visual Analogue Scale at the time immediately after the intervention (0 hours), at the interval of 6 hours of the intervention and after 24 hours of the first laser irradiation, always during the feeding. Data were analyzed descriptively by means of summary measures, chisquare test, Fisher's exact test and Student's ttest. For all statistical tests a significance level of 5% was adopted. Statistical analyzes were performed using SPSS 20.0 and Stata 12. Results: The mean pain grade presented by the postpartum women prior to the interventions was 7.6 in both groups. These behaved similarly to pain reduction after irradiation, of which 1.4 corresponded to the intervention group and 0.9 in the control group, at the moment immediately after the intervention. The perception of pain reduced approximately one point for both groups, and was not statistically different between them. The degree of pain decreased over time in both groups (p <0.001). Sensations of tingling and prickingafter the intervention were reported by the postpartum women and these were considered secondary effects of the therapy. Conclusion: The mean pain grade attributed by postpartum women at the time of inclusion in the study was classified as moderate pain, and no studies in the literature have been identified that address this data numerically for comparison. Irradiation in the proposed protocol for evaluation of the analgesic effect did not show a statistically significant difference immediately after the application, six and 24 hours after irradiation, when compared to the Control group. New lowpotency laser protocols need to be tested in order for this therapy to be beneficial for puerperal patients and to configure a new possibility for the treatment of nipple lesions.